20 ps time resolution with a fully-efficient monolithic silicon pixel detector without internal gain layer. (1st March 2023) - Zambito, S.; Milanesio, M.; Moretti, T.; Paolozzi, L.; Munker, M.; Cardella, R.; Kugathasan, T.; Martinelli, F.; Picardi, A.; Elviretti, M.; Rücker, H.; Trusch, A.; et al.
Abstract: A second monolithic silicon pixel prototype was produced for the MONOLITH project. The ASIC contains a matrix of hexagonal pixels with 100 μm pitch, readout by a low-noise and very fast SiGe HBT frontend electronics. Wafers with 50 μm thick epilayer of 350 Ωcm resistivity were used to produce a fully depleted sensor. Laboratory and testbeam measurements of the analog channels present in the pixel matrix show that the sensor has a 130 V wide bias-voltage operation plateau at which the efficiency is 99.8%. Although this prototype does not include an internal gain layer, the design optimised for timing of the sensor and the front-end electronics provides a time resolutions of 20 ps.